Innovation Of Half Day Tour Package For Beleka Village In Central Lombok NTB - Indonesia - Linda Astuti Handriani; Endang Sri Wahyuni; Muh. Ilham H (International Journal of Geotourism Science and Development, 2024)
Many tour packages are arranged according to the type of tourism that tourists are interested in. Currently, the type of tourism that is popular among local and foreign tourists is regional crafting tours with a touch of local culture or traditions. This tour can be found in Beleka Village, Central Lombok, NTB Indonesia. Beleka Village has a variety of potential tourist attractions, not all of which have been packaged into a tourism package because the role of the village manager is not yet optimal and maximized. This research aims to identify potential tourist attractions aspec in Beleka Village for drafting tour package innovation. This research was carried out using an inductive research approach (theory development), with a choice of qualitative methodology, and a case study research strategy as well as the choice of research time: cross sectional. The data collection and analysis are by using reducing data, display data, and conclusion, as well as data analysis using content analysis which had grouped the data finding into categories or themes. For the validity of the data had used triangulation of methods and sources. Triangulation method are used three methods for gatering qualitative data namely: observation, interviews and documentation. While Triangulation of sources were implemented by interviewing 5 informants. The research results obtained data in the following categories: characteristics, novelty, planned programs, and objectives. After Analysing and processing of these four data categories had provided innovative half day tour packages for Beleka Village. To proven the quality of this Half Day Tour package innovation should be delivered and implemented by the next researcher who is interested in this field.